Expanding the Rule of Law: Judicial Reform in Central Europe & Latin America - Peter J. Messitte (Washington University Global Studies Law Review, 2005)
These remarks explore areas of judicial reform in Europe and Latin America. Particular attention is given to constitutional revisions, the establishment of courts, judicial career laws, trial transparency, and reformed codes of ethics. Despite several shortcomings, this paper optimistically highlights the progress of judicial reform in many countries.
Keywords: Judicial process; Rule of law; Central America; European Union; South America